Linking Dynamic Capabilities and Market Performance of SMEs: The Moderating Role of Organizational Agility - Bulent Akkaya; Qaisar Iqbal (Istanbul Business Research (IBR), 2021)
The purpose of this study is to highlight the moderating role of organizational agility (OA) between dynamic capabilities (DC) and market performance (MP) in SMEs in Turkey and Malaysia. The data was collected from 198 managers in both countries. The data was analyzed by Partial Least Squares Structural Equation Modelling (PLS-SEM). The research has found that there is a significant relationship between organizational agility and market performance, dynamic capabilities and market performance. The finding also reveals that organizational agility has a moderating role between dynamic capabilities and market performance. This research contributes to boosting scientific research, particularly in terms of testing the model content, as well as the variables and the factors affecting them. In addition, this research pointed to the need for organizations to practice organizational agility and dynamic capabilities in order to improve market performance. Dynamic capabilities and organizational agility vary according to environmental dynamism for a firm's market performance and high levels of dynamic capabilities may lead to upper market performance, as market performance is often more directly tied to SMEs organizational agility. Moreover, managers should account for dynamic capabilities while assessing the effects of it on organizational agility and firm performance.
Keywords: 650; Organizational Agility; Dynamic Capabilities; Market Performance; SMEs; Turkey; Malaysia